Aptamer Switches Regulated by Post‐Transition/Transition Metal Ions - Billet, Blandine; Chovelon, Benoit; Fiore, Emmanuelle; Oukacine, Farid; Petrillo, Mel‐Alexandre; Faure, Patrice; Ravelet, Corinne; Peyrin, Eric (Angewandte Chemie International Edition, 2021)
We introduced an aptamer switch design that relies on the ability of post‐transition/transition metal ions to trigger, through their coordination to nucleobases, substantial DNA destabilization. In the absence of molecular target, the addition of one such metal ion to usual aptamer working solutions promotes the formation of an alternative, inert DNA state. Upon exposure to the cognate compound, the equilibrium is shifted towards the competent DNA form. The switching process was preferentially activated by metal ions of intermediate base over phosphate complexation preference (i.e. Pb2+, Cd2+) and operated with diversely structured DNA molecules. This very simple aptamer switch scheme was applied to the detection of small organics using the fluorescence anisotropy readout mode. We envision that the approach could be adapted to a variety of signalling methods that report on changes in the surface charge density of DNA receptors. Structural transition metal ions: Post‐transition/transition metal ions can induce, through their coordination to nucleobases, substantial DNA destabilization. We exploited such property for elaborating fluorescent aptamer probes that switch between inert, metal ion‐complexed and active, target‐bound states. This very simple structural switching strategy was applied to the homogeneous‐phase detection of small organics using diversely structured aptamers.